Perceived barriers and enablers of physical activity in postpartum women: A qualitative approach - Saligheh, M.; McNamara, Beverley; Rooney, Rosanna (BioMed Central Ltd, 2016)
© 2016 Saligheh et al.Background: Postpartum women's recovery from birth can be assisted through increased physical activity (PA). However, women face substantial barriers to participating in exercise and require support to enable them to benefit from increased PA. Methods: This study sought to explore women's beliefs about and experiences of PA and exercise during the 6 weeks to 12 months postpartum period. A cohort of 14 postpartum women from a survey study of the barriers and enablers to exercise participation agreed to take part in interview sessions to provide an in-depth understanding of the women's perceptions of the postpartum period and their physical activity during this time. Results: Findings are presented with reference to the social ecological framework and indicate postpartum women face substantial personal and environmental barriers to PA and exercise participation: fatigue, a lack of motivation and confidence, substantial time constraints, lack of access to affordable and appropriate activities and poor access to public transport. In contrast, enablers such as possessing greater social support, in particular partner support, improved PA and exercise participation. Conclusions: The findings encourage facilitation of exercise through mothers' groups, mothers' exercise clubs or postnatal classes suggesting behavioral and social change is needed. Interaction between individuals, community, organizations and policy makers is required. In addition, the provision of specifically tailored and appropriate exercise programs could potentially enable increased PA in postpartum women, thereby improving their health.